Anthropogenically induced changes in twentieth century mineral dust burden and the associated impact on radiative forcing. Issue 23 (12th December 2014) - Stanelle, Tanja; Bey, Isabelle; Raddatz, Thomas; Reick, Christian; Tegen, Ina
Abstract We investigate the relative importance of climate change (CC) and anthropogenic land cover change (ALCC) for the dust emissions and burden changes between the late nineteenth century and today. For this purpose, the climate‐aerosol model ECHAM6‐HAM2 is complemented by a new scheme to derive potential dust sources at runtime using the vegetation cover provided by the land component JSBACH of ECHAM6. Dust emissions are computed online using information from the ECHAM6 atmospheric component. This allows us to account for changes in land cover and climate interactively and to distinguish between emissions from natural and agricultural dust sources. For today's climate we find that nearly 10% of dust particles are emitted from agricultural areas. According to our simulations, global annual dust emissions have increased by 25% between the late nineteenth century and today (e.g., from 729 Tg/a to 912 Tg/a). Globally, CC and ALCC (e.g., agricultural expansion) have both contributed to this change (56% and 40%, respectively). There are however large regional differences. For example, change in dust emissions in Africa are clearly dominated by CC. Global dust burden have increased by 24.5% since the late nineteenth century, which results in a clear‐sky radiative forcing at top of the atmosphere of −0.14 W/m2. Based on these findings, we recommend that both climate changes and anthropogenic land cover changes should be considered when investigating long‐term changes in dust emissions.